PENGEMBANGAN BAHAN AJAR BERBASIS KONSTRUKTIVISME PADA MATAKULIAH STATISTIKA EKONOMI - Ria Deswita (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
This research is motivated by the important of statistics, especially in the economics. Therefore, students must know economic statistics. The reality shows that students' ability in economic statistics  is still low. In order that this problems can be solved, a learning module that can help students in studying economic statistics is required. Therefore, in this research the  learning module based on constructivism was selected. This research aims to develop learning module based on constructivism in economic statistics courses. This research is a development research with the ADDIE  model. The subject is students of the Islamic Economics Department, Faculty of Economics and Islamic Business, IAIN Kerinci. This research used two instruments: validation sheets and student response questionnaires. Based on the data analyse, it is found that:  1) The learning module based on constructivism was valid in terms of material, appearance, and constructivism, 2) The learning module based on constructivism wast practical in terms of usefulness, attractiveness, and efficiency with a proportion of 85%